Micronuclei frequency in lymphocytes of individuals occupationally exposed to pesticides - Ramírez, Vanessa (Universidad de Costa Rica, 2001)
Pesticides have been widely used in developing countries over the years. A large amount of these remains in the environment and organisms. Pesticide pollution is detrimental to human health. The effects can be seen on a short or a long-term basis and the symptoms can vary from headache to cancer. Only a minority of studies focuses on their genotoxic effect. This study assesses the genotoxic effect of the pesticides used at banana-packaging plants with binucleate micronuclei assay using cultured lymphocytes. The studied population included 32 exposed and 37 unexposed women from Costa Rica. There is no significant difference between the two groups. However, women who worked at the packaging plant and had stillbirths or spontaneous abortions were 1.45 times more (α = 0.06) likely to have an increased micronuclei frequency than their coworkers who lacked those disorders; this may indicate genetic susceptibility. In vitro pesticides studies and susceptibility biomarkers are needed to identify subgroups with higher risks.